A systematic review of the literature on mechanisms of 5-nitroimidazole resistance in Trichomonas vaginalis. Issue 13 (30th November 2020) - Graves, Keonte J.; Novak, Jan; Secor, W. Evan; Kissinger, Patricia J.; Schwebke, Jane R.; Muzny, Christina A.
Abstract: Background: Trichomonas vaginalis is the most common non-viral sexually transmitted infection. 5-Nitroimidazoles [metronidazole (MTZ) and tinidazole (TDZ)] are FDA-approved treatments. To better understand treatment failure, we conducted a systematic review on mechanisms of 5-nitroimidazole resistance. Methods: PubMed, ScienceDirect and EMBASE databases were searched using keywords Trichomonas vaginalis, trichomoniasis, 5-nitroimidazole, metronidazole, tinidazole and drug resistance. Non-English language articles and articles on other treatments were excluded. Results: The search yielded 606 articles, of which 550 were excluded, leaving 58 articles. Trichomonas vaginalis resistance varies and is higher with MTZ (2.2–9.6%) than TDZ (0–2%). Resistance can be aerobic or anaerobic and is relative rather than absolute. Differential expression of enzymes involved in trichomonad energy production and antioxidant defenses affects 5-nitroimidazole drug activation; reduced expression of pyruvate:ferredoxin oxidoreductase, ferredoxin, nitroreductase, hydrogenase, thioredoxin reductase and flavin reductase are implicated in drug resistance. Trichomonas vaginalis infection with Mycoplasma hominis or T. vaginalis virus has also been associated with resistance. Trichomonas vaginalis has two genotypes, with greater resistance seen in type 2 ( vs type 1) populations. Discussion: 5-Nitroimidazole resistance results from differential expression of enzymes involved in energy production or antioxidant defenses, along with genetic mutations in the T. vaginalis genome. Alternative treatments outside of the 5-nitroimidazole class are needed.